2008
DOI: 10.1007/s11740-008-0112-6
|View full text |Cite
|
Sign up to set email alerts
|

Material adapted tool design in cold forging exemplified by powder metallurgical tool steels and industrial ceramics

Abstract: The advantages of today's cold forging technology, such as excellent mechanical properties of the workpiece and minimum waste of material together with energy saving via near net shaping increase its competitiveness against other production methods. However, as a result of extremely high loading of the tools when compared with warm and hot forging, tool life is distinctly more confined resulting in increased production costs. Due to separately or concurrently emerging damaging mechanisms of fatigue and wear at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In cold forging, wear of tools is very high in comparison to warm and hot forging so die material is an important aspect to be considered for tool life improvement. Geiger et al [ 129 ] did a case study on application of ceramic coating (Si 3 N 4 ) on stainless steel. It was observed that with increase in forging load, the ceramic coating had developed cracks due to concentration of tensile strains.…”
Section: Methods To Enhance the Tool Lifementioning
confidence: 99%
“…In cold forging, wear of tools is very high in comparison to warm and hot forging so die material is an important aspect to be considered for tool life improvement. Geiger et al [ 129 ] did a case study on application of ceramic coating (Si 3 N 4 ) on stainless steel. It was observed that with increase in forging load, the ceramic coating had developed cracks due to concentration of tensile strains.…”
Section: Methods To Enhance the Tool Lifementioning
confidence: 99%
“…There are many advantages of cold forging, such as excellent mechanical properties of the forged part, minimum material wastage, and the ability to forge a net shape or near-net shape product. However, the cold forging tools are subjected to a combination of abrasive wear and very high mechanical loads, which generates a surface pressure of up to 3000 MPa that is caused by high flow stress of the billet material at room temperature [2,3]. Overstressing of the tool, abrasive wear, galling or adhesive wear, and fatigue failure are common failure modes of cold forging tools [4].…”
Section: Introductionmentioning
confidence: 99%